PERSEPSI SISWA KELAS VI SD TERHADAP GURU PAK DALAM PEMBENTUKAN ETIKA DAN MORAL - Yeremia I. Nitano; Steaven Octavianus (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2021)
The purpose of this research is to find out the perception of sixth graders towards Christian Education teachers in the matters of ethics and morals teaching. This research was conducted so that violence in the learning process will not occur in the learning process. The method used in this research is descriptive analysis method with a qualitative approach. The data analysis technique used is data triangulation, while for the data collection techniques are interviews, field observations and documentation. Students' perception is that how students see that Christian Education teachers use violence in the teaching and learning process, especially in the process of Christian ethics and morals teaching, students see that Christian Education teachers in teaching must be focus on the teaching responsibility. Students see that Christian Education teachers still smoke and consume alcohol. Students see that the teacher does not a good role model on ethics and morals as Christians in church and society.